The Bone-Forming Properties of Periosteum-Derived Cells Differ Between Harvest Sites - Groeneveldt, Lisanne C.; Herpelinck, Tim; Maréchal, Marina; Politis, Constantinus; van IJcken, Wilfred F. J.; Huylebroeck, Danny; Geris, Liesbet; Mulugeta, Eskeatnaf; Luyten, Frank P. (Frontiers in Cell and Developmental Biology, 2020)
The development of alternatives for autologous bone grafts is a major focus of bone tissue engineering. To produce living bone-forming implants, skeletal stem and progenitor cells (SSPCs) are envisioned as key ingredients. SSPCs can be obtained from different tissues including bone marrow, adipose tissue, dental pulp, and periosteum. Human periosteum-derived cells (hPDCs) exhibit progenitor cell characteristics and have well-documented in vivo bone formation potency. Here, we have characterized and compared hPDCs derived from tibia with craniofacial hPDCs, from maxilla and mandible, respectively, each representing a potential source for cell-based tissue engineered implants for craniofacial applications. Maxilla and mandible-derived hPDCs display similar growth curves as tibial hPDCs, with equal trilineage differentiation potential toward chondrogenic, osteogenic, and adipogenic cells. These craniofacial hPDCs are positive for SSPC-markers CD73, CD164, and Podoplanin (PDPN), and negative for CD146, hematopoietic and endothelial lineage markers. Bulk RNA-sequencing identified genes that are differentially expressed between the three sources of hPDC. In particular, differential expression was found for genes of the HOX and DLX family, for SOX9 and genes involved in skeletal system development. The in vivo bone formation, 8 weeks after ectopic implantation in nude mice, was observed in constructs seeded with tibial and mandibular hPDCs. Taken together, we provide evidence that hPDCs show different profiles and properties according to their anatomical origin, and that craniofacial hPDCs are potential sources for cell-based bone tissue engineering strategies. The mandible-derived hPDCs display - both in vitro and in vivo - chondrogenic and osteogenic differentiation potential, which supports their future testing for use in craniofacial bone regeneration applications.